مفهوم دار الحرب في فقه الإسلامي - Ahmad, Abdullah Abu Bakr (DINIKA : Academic Journal of Islamic Studies, 2019)
This research aims to give the reader a comprehensive view of the concept of Dar al-Harb according to sharia Islamic Law. The first and foremost is to explain some of its terminologies, it defines the concept of Dar al-Harb (state of war) literally and technically. Then it combines the concept of the House of the Covenant and the raising of forms from the terms Dar al-Harb (state of war) and Dar al-Islam (Islamic state). It concludes by mentioning what the house becomes as the house of Islam and vice versa. The research concluded that  - The House of Islam does not turn in any case from the whole situation to the house of Kufr unless proven and verify that most of the inhabitants are infidels or apostates, and showed the provisions of the infidels and went from the country and all the features and rituals of the Islamic religion as occurred in Andalus. At the end, the conclusion drawn from variant views of the scholars and the main findings and recommendations have been given.